APAKAH INVESTOR SAHAM MENDERITA MYOPIC LOSS AVERSION? EKSPERIMEN - wendy . (Jurnal Bisnis dan Ekonomi, 2010)
This study explores the psychology of bias experienced stock investors when making investmentdecision. Through the within-subject experimental design, researchers conducted manipulation ontwo different tritmen conditions (frequent and infrequent), which refers to the theory of myopicloss aversion (MLA). The experimental results show a consistency to the theory of stock investorsMLA. Analysis of gender showed a similarity in terms of investor behavior between male andfemale investors. Other findings show the existence of "shock effect" experienced by the investors.Keywords: behavioral finance, myopic loss aversion, gender, and shock effect